Prospects for the Transfer of Intelligent Solutions for a Smart City - K. S. Astankov; A. S. Nikolaev; S. V. Suvvi (Цифровая трансформация)
An analysis of intelligent solutions for all types of V2X technologies communications was carried out the through patent search and development of the patent landscape. To analyze the patent activity, a domain model was compiled, on the basis of which patenting trends over the past 20 years were determined and the dynamics of patent activity were formed taking into account the legal statuses. The distribution of patents among the leading companies has been identified, and the geography of patenting has been determined.